Tonsillectomies and respiratory complications in children: A look at pre-op polysomnography risk factors and post-op admissions. (September 2016) - Kasle, David; Virbalas, Jordan; Bent, John P.; Cheng, Jeffrey
Abstract: Objective: To identify predictors of post-operative respiratory complications in children undergoing tonsillectomy. Methods: Consecutive case series with chart review of children who underwent polysomnography (PSG) and subsequent tonsillectomy with or without adenoidectomy for obstructive sleep apnea (OSA). Patients with craniofacial anomalies or significant cardiopulmonary comorbidities were excluded. Rates of post-surgical respiratory complication were reviewed and compared to patient specific factors and PSG findings to identify possible risk factors. Results: Eighty-six patients (mean age 5.3 ± 2.2 years) were included. There was a statistically significant (p = 0.03) relationship between an AHI ≥40 (AHI40) and post-operative respiratory complications. AHI40 also had the greatest magnitude of association with postoperative respiratory complications (OR = 5.313). An AHI ≥25 (AHI25) was marginally significant (p = 0.067). No significant difference in outcome occurrence was found when analyzing rates of complication in patients with BMI above and below 18 (p = 0.20) or oxygen (O2) nadir above and below 80% (p = 0.09). The AHI ranged from 0 to 112.2, and no postoperative respiratory complications were identified in children with an AHI less than 10. Conclusions: Our results indicate an association between an AHI ≥40 and respiratory complications following an adenotonsillectomy, but we were not able to observe any significant difference at a cutoff of 25. An association between BMI or O2 nadir and postoperative respiratory complication was not able to be identified. Our results support the importance of AHI as a predictor of postoperative respiratory complications in children undergoing tonsillectomy for OSA.